Simulation of Climate Change Effects on Hydropower Operations in Mountain Headwater Lakes, New Zealand. (18th July 2016) - Caruso, B. S.; King, R.; Newton, S.; Zammit, C.
Abstract: Future climate change is expected to have wide ranging impacts on the hydrology of mountain rivers because of changes in the magnitudes and timing of rain and snow, as well as the significant spatial variability of topography and other catchment characteristics. In New Zealand, hydropower generation in mountain basins is the primary source of electricity and renewable energy resource in the country. The goal of this study was to simulate and evaluate the potential effects of climate change on hydropower operations in three mountain headwater lakes (lakes Pukaki, Tekapo, and Ohau) in the Upper Waitaki Basin of the central South Island. The TopNet hydrological model was used to estimate catchment runoff and lake inflows based on the 1990s (baseline), 2040s, and 2090s periods. Average temperature and precipitation results from an ensemble of 12 Global Circulation Models based on the IPCC 4th Assessment Report A1B emissions scenario were used as input to TopNet. Linked hydropower lake water balance models were developed and used to simulate hydropower operations including discharge, hydroelectric power generation, and spill based on TopNet future inflow predictions, projected electricity demand, and lake storage and outflow characteristics. Our results indicate that annual lake inflows increase under future climate scenarios, but that there are seasonal effects with increasing flows in winter and early spring, and summer flows decreasing somewhat as a result of increasing temperatures and greater winter rain with less snow. Although overall hydropower generation can increase with the increasing flows and projected electricity demand, the seasonal changes result in demand being met in winter and spring with potential shortfalls in summer and autumn. Maximum annual generation can be achieved for some generating stations, but generation will decrease at other stations and more spill will likely be required through the 2090s because of the seasonal changes. Therefore flood and drought risk could also increase for downstream areas. Results also indicate that by the 2090s electricity demand could exceed generation capacity for these headwater lakes. Copyright © 2016 John Wiley & Sons, Ltd.